Mechanism of a motion platform inducing the movement of the operator`s seat in a heavy machine - Tora, Grzegorz; Trzaska, Witold (Zielona Góra: Uniwersytet Zielonogórski)
One of the major work safety issues involves the investigations of machine vibrations and the way they affect the machine operators. These investigations can be performed in the laboratory conditions in a setup in which the seat vibrations are induced by a motion platform. A complex mechanism is proposed implementing 3 translations and 2 rotation movements, and actuated by three electric motors. This study investigates the design structure of the real motion platform mechanism and provides the synthesis of link dimensioning. Kinematic dependencies are formulated and the Jacobian matrix is derived accordingly to solve the equations of motion. Computer simulation procedure yields the critical seat vibration frequency and amplitudes for the available asynchronous motors.
Keywords: simulator; synthesis; modeling of the mechanism